How critical junctures shape secessionist movement cohesion: Strategies, framing processes, and interorganizational relations before and after the 2017 referendum in Catalonia - Hans Jonas Gunzelmann (Journal of Peace Research, 2024)
What drives the cohesion of secessionist movements? Previous research emphasized the role of internal and external factors but produced mixed results regarding their effects. This article advances scholarship on this question by examining the role of critical junctures as periods of heightened contingency that can shift movements towards fragmentation or cohesion. It focuses on independence referendums and how states respond to them as important critical junctures, and on how they shape interorganizational relations as a key dimension of movement cohesion. Empirically, it explores the effects of the 2017 referendum in Catalonia using a mixed-methods research design that combines qualitative inquiry with network analyses of protest event data. The network analyses showed that the movement was notably less cohesive in the protest arena after the referendum than during the referendum campaign. Qualitative materials were employed to inductively identify strategy framing processes as key mechanisms to explain this development. Frame alignment around the referendum as a shared goal led to more cohesion during the campaign. After the event, a frame dispute over the meaning of the referendum led to diverging strategies and fragmented the movement, as state repression limited the movement's room for maneuver. The findings suggest that research on secessionist movement cohesion should pay more attention to critical junctures and how secessionists make sense of them.
Keywords: 320; Catalonia; fragmentation; frame alignment; independence referendum; networks; secessionist movements